2016
DOI: 10.1073/pnas.1524384113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular requirements for a pandemic influenza virus: An acid-stable hemagglutinin protein

Abstract: Influenza pandemics require that a virus containing a hemagglutinin (HA) surface antigen previously unseen by a majority of the population becomes airborne-transmissible between humans. Although the HA protein is central to the emergence of a pandemic influenza virus, its required molecular properties for sustained transmission between humans are poorly defined. During virus entry, the HA protein binds receptors and is triggered by low pH in the endosome to cause membrane fusion; during egress, HA contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
210
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(228 citation statements)
references
References 42 publications
15
210
0
Order By: Relevance
“…As shown in Fig. 4, NY/108 virus was able to induce syncytia at pH values of Յ5.4, comparable to recent 2009 pandemic A(H1N1) viruses (35). In contrast, other H7 viruses, including the avian LPAI H7N2 virus Tky/VA and the human LPAI H7N9 virus A/Anhui/ 1/2013 (Anhui/1), had a higher pH threshold (pH Յ 5.8) for fusion.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…As shown in Fig. 4, NY/108 virus was able to induce syncytia at pH values of Յ5.4, comparable to recent 2009 pandemic A(H1N1) viruses (35). In contrast, other H7 viruses, including the avian LPAI H7N2 virus Tky/VA and the human LPAI H7N9 virus A/Anhui/ 1/2013 (Anhui/1), had a higher pH threshold (pH Յ 5.8) for fusion.…”
mentioning
confidence: 62%
“…It has recently been shown that adaptation of avian influenza viruses to mammals is often associated with a decrease in the HA activation threshold and that an acid-stable HA is necessary for the generation of an airborne transmissible H5 influenza virus (32)(33)(34)(35). Like most avian influenza viruses, avian-origin H7 viruses fuse at relatively high pH values compared to those for human seasonal influenza viruses (36).…”
mentioning
confidence: 99%
“…There is evolutionary pressure that balances the number of trimers required for fusion, the rate at which the trimers activate, and the specific pH optimum of activation [100]. These reflect a balance between transmission stability in acidic environments, which contributes to potency to cause pandemics [118], and the location of viral RNA release in the infected cell. This location can be an early endosome, far from the nuclear target, or close to the target in a late endosome, with a higher risk of HA degradation by enzymes [100].…”
Section: Open Questions and Future Experimentsmentioning
confidence: 99%
“…Influenza viruses with unstable HA replicate less well in the upper respiratory tract of ferrets, the most representative animal model. 54 A stabilising mutation present in more recent pH1N1 isolates but not the earliest strains from 2009 was associated with greater infectivity in the ferret nasal tract. 55 O'Donnell et al 56 demonstrated that viruses reassorted to contain "Ann Arbor" internal genes became less pH stable than their wild-type counterparts due to cold-adapting mutations in the viral M gene.…”
Section: (Iii)biological Characteristics Of the Ph1n1 Virus (A)reducementioning
confidence: 90%
“…52 By summer 2009, the emerging pH1N1 virus had achieved the minimal requirements to overcome the initial host range barriers, but was far from a fully human-adapted virus. Over the next few years pH1N1 has accumulated further 'humanizing' mutations and become more acid stable, 53,54 but the virus is still not as fine-tuned to its new host as the human-specific influenza B viruses or H3N2 viruses that have circulated in humans since 1968. Thus, immunogenicity of LAIV with pH1N1 HA and NA antigens might be lower than for the other vaccine components because replication in the target tissue is lower.…”
Section: (Iii)biological Characteristics Of the Ph1n1 Virus (A)reducementioning
confidence: 99%